2022
DOI: 10.1155/2022/6361256
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0078767 Inhibits the Progression of Non-Small-Cell Lung Cancer by Regulating the GPX3 Expression by Adsorbing miR-665

Abstract: Non-small-cell lung cancer (NSCLC) is one of the most serious cancers. The circular RNA_0078767 (circ_0078767) expression was decreased in NSCLC tissues. However, the molecular mechanism of circ_0078767 remains unknown. The expression of circ_0078767, microRNA-665 (miR-665), and glutathione peroxidase 3 (GPX3) was detected by quantitative real-time fluorescence polymerase chain reaction (qRT-PCR). Cell proliferation, migration, and invasion were detected by colony formation assay and transwell assay, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Several studies have indicated that GPX3 plays a tumor-suppressive role in NSCLC by repressing tumor cell proliferation, migration, and invasion. For instance, downregulation of miR-196a could upregulate GPX3, which results in inactivation of the c-Jun N-terminal kinase (JNK) signaling pathway, leading to a decline in stemness, self-renewal capacity, and tumorigenicity of NSCLC [48]; a high expression of GPX3 could inhibit the malignant biological behaviors of NSCLC cells by modulating the miR-665/GPX3 signaling pathways [49], and overexpression of GPX3 could signi cantly inactivate reactive oxygen species, thereby repressing the Erk-NF-κB-cyclin B1 signaling pathway and causing cell cycle arrest [50]. However, interestingly, polarized alveolar type 2 epithelial cells highly expressed GPX3 and abundantly produced interleukin-10, thus inhibiting CD4 + T cell proliferation and enhancing regulatory T cell generation, eventually leading to the formation of a premetastatic niche required for metastasis [51].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that GPX3 plays a tumor-suppressive role in NSCLC by repressing tumor cell proliferation, migration, and invasion. For instance, downregulation of miR-196a could upregulate GPX3, which results in inactivation of the c-Jun N-terminal kinase (JNK) signaling pathway, leading to a decline in stemness, self-renewal capacity, and tumorigenicity of NSCLC [48]; a high expression of GPX3 could inhibit the malignant biological behaviors of NSCLC cells by modulating the miR-665/GPX3 signaling pathways [49], and overexpression of GPX3 could signi cantly inactivate reactive oxygen species, thereby repressing the Erk-NF-κB-cyclin B1 signaling pathway and causing cell cycle arrest [50]. However, interestingly, polarized alveolar type 2 epithelial cells highly expressed GPX3 and abundantly produced interleukin-10, thus inhibiting CD4 + T cell proliferation and enhancing regulatory T cell generation, eventually leading to the formation of a premetastatic niche required for metastasis [51].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase 3 (Gpx3) is an antioxidant enzyme, the only exocrine form of glutathione peroxidase family, which acts in detoxi cation of hydrogen peroxide to shields cells and enzymes from oxidative damage and regulates redox 19 . Besides, as a tumor suppressor gene, Gpx3 is involved in the occurrence of a variety of cancer diseases 20 , including ovarian cancer, breast cancer 21 , thyroid cancer 22 and lung cancer 23 . Furthermore, Gpx3 is also a tumor suppressor gene in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Famously, circRNAs can participate in the post-transcriptional regulation of coding gene expression in cancer by acting as microRNA (miRNA) sponges ( 8 ). The significance of circRNAs in the pathogenesis of NSCLC has been established ( 9 , 10 ). CircRNA (circ)_0087378 has been recently identified to be down-regulated in breast cancer; it suppressed the progression of breast cancer by elevating secreted frizzled related protein-1 (SFRP1) expression via sponging miRNA (miR)-1260b ( 11 ).…”
Section: Introductionmentioning
confidence: 99%